2019
DOI: 10.1080/02615479.2019.1570108
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, dialogue, and identity in designing globally relevant social work education

Abstract: The Erasmus Mundus ADVANCES Master program has been funded with support from the Education, Audiovisual and Culture Executive Agency of the European Commission under Grant FPA 2013-0242. This publication reflects the views only of the authors, and the Commission cannot be held responsible for any use which may be made of the information contained therein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In the 2019 study by Rasell et al of a two-year multiethnic social work program, with an approximate intake of 17 students per cohort, interconnected with five International Universities [23], the most interesting aspect of this research suggested that 'The 'international' acts as a frame of reference for studies rather than a particular body of knowledge and skills to be transmitted to students ' (p.14). In all, this seems a fair goal but its delivery may prove more challenging.…”
Section: Globalization and Indigenizationmentioning
confidence: 92%
See 2 more Smart Citations
“…In the 2019 study by Rasell et al of a two-year multiethnic social work program, with an approximate intake of 17 students per cohort, interconnected with five International Universities [23], the most interesting aspect of this research suggested that 'The 'international' acts as a frame of reference for studies rather than a particular body of knowledge and skills to be transmitted to students ' (p.14). In all, this seems a fair goal but its delivery may prove more challenging.…”
Section: Globalization and Indigenizationmentioning
confidence: 92%
“…The aim for a healthier society is to achieve sustainable, collaborative outcomes which, influenced by the skills of social work professionalism, creates a variety of multi-faceted, pragmatic solutions to highly complex problems, both individual and social [19,20]. Further studies on global agendas and international social work are covered in Jones and Truell [21], Doel et al [22] and Russell et al [23]. British social work academic Lisa Dominelli also turns her attention to globalization and professional practices (see [24]) informing the more recent publication of 'Global social work in a Political context: Radical Perspectives' by Ferguson et al [25].…”
Section: Globalization and Indigenizationmentioning
confidence: 99%
See 1 more Smart Citation